2018
DOI: 10.18632/oncotarget.24389
|View full text |Cite
|
Sign up to set email alerts
|

Cell internalization of 7-ketocholesterol-containing nanoemulsion through LDL receptor reduces melanoma growth in vitro and in vivo: a preliminary report

Abstract: Oxysterols are cholesterol oxygenated derivatives which possess several biological actions. Among oxysterols, 7-ketocholesterol (7KC) is known to induce cell death. Here, we hypothesized that 7KC cytotoxicity could be applied in cancer therapeutics. 7KC was incorporated into a lipid core nanoemulsion. As a cellular model the murine melanoma cell line B16F10 was used. The nanoparticle (7KCLDE) uptake into tumor cells was displaced by increasing amounts of low-density-lipoproteins (LDL) suggesting a LDL-receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 61 publications
0
9
0
5
Order By: Relevance
“…Paclitaxel (PTX) is an anticancer drug often used to treat lung, breast, pancreatic, and ovarian cancer. It has the ability to interfere with the breakdown of microtubules during cellular division, leading to apoptosis, mitotic arrest, and inhibition of cell functions [108]. PTX has very low water solubility, which is why many formulations, like Taxol ® containing Cremophor-EL ® and ethanol, have been developed.…”
Section: Nanoemulsions Applied To Cancer Therapymentioning
confidence: 99%
“…Paclitaxel (PTX) is an anticancer drug often used to treat lung, breast, pancreatic, and ovarian cancer. It has the ability to interfere with the breakdown of microtubules during cellular division, leading to apoptosis, mitotic arrest, and inhibition of cell functions [108]. PTX has very low water solubility, which is why many formulations, like Taxol ® containing Cremophor-EL ® and ethanol, have been developed.…”
Section: Nanoemulsions Applied To Cancer Therapymentioning
confidence: 99%
“…These properties led us to investigate the potential use of oxysterols as chemotherapeutic agents in cancer [23]. Our results showed that 7-ketocholesterol (7-KC), a well-known oxysterol, had cytostatic and cytotoxic effects on melanoma, in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 94%
“…Outra via de morte celular que pode ser presenciada nas células tratadas com oxisteróis é a necrose, que foi observada tanto em experimentos in vitro como in vivo (Favero et al, 2018;Silva et al, 2016). A necrose, pode ser identificada através do inchaço celular que leva ao rompimento da membrana plasmática e consequentemente ao extravasamento do conteúdo celular (Yamanaka et al, 2011).…”
Section: Vias De Morte Celularunclassified
“…Porém, em outro estudo, foi possível observar que os oxisteróis citotóxicos foram capazes de inibir a fase S do ciclo celular e estimular a fase G0/G1 ou a fase G2/M em linhagem de câncer de mama (Levy et al, 2018). Em outro trabalho foi observado uma redução do tamanho da área tumoral em mais de 50 %, em modelo de melanoma murino (Favero et al, 2018). O presente trabalho visa estudar as características da morte de células-tronco mesenquimais de medula óssea de pacientes com leucemia mieloide aguda promovida por oxisteróis.…”
Section: Transportadores Abcsunclassified
See 1 more Smart Citation